Polish books (collections) in the libraries of Rome - Henczel-Wróblewska, Ligia ALeksandra (Folia Toruniensia, 2017)
The Polish-Italian contacts have a long history. From the very Middle Ages, when Polish scholars started to study in Italian universities, they centered around science and education. In the subsequent ages the mutual contacts also included the artistic field, when Polish artists used to go to Italy to master their skills with the best teachers. From the end of the 18th century to the mid-20th century the cooperation also included the military, social-political and economic aspects. In Italy Poles took part in the struggle for independence leading to the Union of Italy ( the Risorgimiento period), and later in the fights during both world wars. Since the mid-20th century Italy and Poland have maintained bilateral contacts in various fields. In all those periods the Polish presence in Italy was recorded in written, iconographic and artistic sources. Most of them are preserved in archives and libraries in Rome – the centre of European science, culture and Christianity. It was not until the 20th century, when the first scientific Polish institutions were set up in Rome, that it became possible to register, compile and sort out Polonicas found in Rome’s libraries, archives, cultural institutions, and private collections. Written monuments indicate a number of associations both in the sacrum and profanum spheres. The common heritage of historical memory is the evidence of Poland’s belonging to the European community for a long time.